Comparative performance of PtRu/C catalysts synthesized by different methods for direct methanol fuel cells under various operating conditions - Souza, Elson Almeida De; Silva, Rudyere Nascimento; Gonçalves, Daniel A.; Pocrifka, Leandro Aparecido; Passos, Raimundo Ribeiro (Frontiers in Nanotechnology, 2024)
This work presents a comparative study of three synthesis methods for PtRu/C catalysts for use in polymer electrolyte fuel cells, investigating their activity in methanol oxidation. The evaluated methods were formic acid reduction (FAM), methanol reduction (ARM), and ethylene glycol reduction (ARE). XRD analysis confirmed the formation of a Pt-Ru binary alloy in all syntheses. Electrochemical tests indicated that all catalysts were properly prepared, with the PtRu/CARE catalyst standing out as having the best performance, achieving a power density of 74,88 mW cm−2 at 90°C and an oxygen pressure of 3 atm on the cathode. These results highlight the potential of PtRu/CARE for application in direct methanol fuel cells, surpassing the catalysts obtained through the other methods.